2006
DOI: 10.1038/sj.jp.7211436
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a point-of-care direct spectrophotometric method for measurement of total serum bilirubin in term and near-term neonates

Abstract: Objective: To evaluate point-of-care (POC) measurement of total serum bilirubin (TSB) in the management of neonatal jaundice.Study design: TSB was measured by a POC direct spectrophotometric bilirubin method (Unistatt (U/TSB)) and a standard diazo clinical laboratory method (Olympus AU640E analyzer (diazo/TSB)). Agreement between U/TSB and diazo/TSB was assessed by correlation coefficient and Bland-Altman analysis. Transcutaneous bilirubin (TcB) was measured using JM-103t (JM).Results: Correlation between U/TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The estimated cost of materials for the prototype reader is less than EUR 150, plus a few cents for each test strip. Newer ‘on-site’ systems utilizing blood gas analyzers [22] or spectrophotometry [23] are more costly, immobile (and hence not truly point-of-care) and may require blood centrifugation.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated cost of materials for the prototype reader is less than EUR 150, plus a few cents for each test strip. Newer ‘on-site’ systems utilizing blood gas analyzers [22] or spectrophotometry [23] are more costly, immobile (and hence not truly point-of-care) and may require blood centrifugation.…”
Section: Discussionmentioning
confidence: 99%
“…Advantages of the noninvasive measuring technique are real-time results, cost-eff ectiveness and avoidance of pain and local infection. Minolta JM-103 TcB assessment demonstrates signifi cant accuracy compared to TSB and can be used as a screening test to identify the need for blood sampling for TSB levels in term and near-term newborn infants [3][4][5][6][7] . Ho et al (2006) reported that combining the use of TcB JM-103 and the 75th centile in Bhutani's nomogram as the cut-off level can identify all cases of signifi cant hyperbilirubinemia in term and near-term newborns 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The remaining sample was centrifuged to separate plasma, and the TSB was measured by a laboratory reference standard using the direct spectrophotometric method for measuring total bilirubin (UNISTAT; Reichert Technologies). The UNISTAT has been shown to have strong correlation with diazo measurement of TSB with a mean difference of −0.37 mg/dL and mean absolute difference of 0.60 mg/dL ( 12 ). After spotting blood on the collection pad, the lateral flow cards were allowed to flow for 2 min and then absorbance was measured using a laboratory spectrometer (Cary 5000 UV-VIS; Agilient).…”
Section: Resultsmentioning
confidence: 99%
“…After the collection pad was filled, the nurse collected additional drops of blood into a tube. Collected blood was centrifuged (2,000 g , 5 min) Galaxy MiniStar; VWR) and plasma was then pipetted out of the sample and measured using the UNISTAT bilirubinometer laboratory reference standard described earlier ( 12 ).…”
Section: Resultsmentioning
confidence: 99%